IMPLEMENTASI MANAJEMEN KEUANGAN PADA MADRASAH ALIYAH AL-QODIR SLEMAN - Nely Fatimmatul Karomah; Tamama Zuhriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Financial management in madrasahs is a critical component in advancing these institutions. The implementation of financial management should be effective, accountable, and transparent. Good financial management ensures that the institution can achieve its goals and provide quality education. The aim of this research is to examine the implementation of financial management in madrasahs. The research methodology employs a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. The data analysis used consists of data condensation, data display, and drawing and verifying conclusions. The validity of the data is tested through source triangulation. The results of the research indicate that financial management in madrasahs is still centralized under the auspices of the Foundation, and the implementation of financial management at MA Al Qodir has not been well-organized or systematic. This is evidenced by the financial management processes not aligning with theories related to financial management. Additionally, there are many obstacles in expenditures and bookkeeping.